2020
DOI: 10.1051/0004-6361/202038574
|View full text |Cite
|
Sign up to set email alerts
|

An extremely hot white dwarf with a rapidly rotating K-type subgiant companion: UCAC2 46706450

Abstract: The subgiant UCAC2 46706450 is a late-type star with an ultraviolet (UV) excess. It was considered as a candidate to establish a sample of stars of spectral type F, G, and K with white dwarf (WD) companions that could be used to test binary evolution models. To verify the WD nature of the companion, UV spectroscopy has previously been performed by other authors. Via a detailed model-atmosphere analysis, we show that the UV source is an extremely hot WD with an effective temperature of Teff = 105 000 ± 5000 K, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 98 publications
0
5
0
Order By: Relevance
“…The identification of WD+AFGK binary candidates has been pioneered by Parsons et al (2016) and Rebassa-Mansergas et al (2017) who cross-matched AFGK-type stars spectroscopically confirmed by the RAVE and LAMOST surveys respectively, with the GALEX ultraviolet photometry. Parsons et al (2016) obtained HST spectroscopy of nine of these potential WD+AFGK binaries, all of which contained white dwarfs (see also Werner et al 2020). 4 Follow-up spectroscopy of TGAS-selected WD+AFGK candidates led to the confirmation of 23 PCEBs (Ren et al 2020, hereafter the "Ren sample").…”
Section: Establishing the Gold Samplementioning
confidence: 99%
“…The identification of WD+AFGK binary candidates has been pioneered by Parsons et al (2016) and Rebassa-Mansergas et al (2017) who cross-matched AFGK-type stars spectroscopically confirmed by the RAVE and LAMOST surveys respectively, with the GALEX ultraviolet photometry. Parsons et al (2016) obtained HST spectroscopy of nine of these potential WD+AFGK binaries, all of which contained white dwarfs (see also Werner et al 2020). 4 Follow-up spectroscopy of TGAS-selected WD+AFGK candidates led to the confirmation of 23 PCEBs (Ren et al 2020, hereafter the "Ren sample").…”
Section: Establishing the Gold Samplementioning
confidence: 99%
“…Magnetically active (sub-)giants, for example, show chromospheric emission lines in Hα, but at the same time also in the cores of the Ca ii H and K lines, as well as sometimes other lines in the optical or ultraviolet (Wilson 1963(Wilson , 1968Gray & Corbally 2009). For some of these stars, time-variability in the chromospheric Hα emission, which is not correlated to the rotation period, has also been reported, though, the exact origin of the variability is not yet understood (e.g., Dorren et al 1984;Vida et al 2015;Kővári et al 2019;Werner et al 2020).…”
Section: Mjd Instrument B (Mg)mentioning
confidence: 99%
“…Moreover, none of the central stars of the sample of large old PNe derived above reaches this luminosity-temperature domain in the Hertzprung-Russell diagram. We conclude that such a luminous white dwarf, even if masked by a main-sequence star in a binary system (e.g., UCAC2 46706450; Werner et al 2020), would not be missed at this low distance and the complete coverage of the region by GALEX.…”
Section: A Nearby Pnmentioning
confidence: 80%